Mixed ice accretion on aircraft wings - Janjua, Zaid A.; Turnbull, Barbara; Hibberd, Stephen; Choi, Kwing-So (American Institute of Physics, 2018)
Ice accretion is a problematic natural phenomenon that an effects a wide range of engineering applications including power cables, radio masts and wind turbines. Accretion on aircraft wings occurs when supercooled water droplets freeze instantaneously on impact to form rime ice or runback as water along the wing to form glaze ice. Most models to date have ignored the accretion of mixed ice, which is a combination of rime and glaze. A parameter we term the `freezing fraction', is defined as the fraction of a supercooled droplet that freezes on impact with the top surface of the accretion ice to explore the concept of mixed ice accretion. Additionally we consider different `packing densities' of rime ice, mimicking the different bulk rime densities observed in nature. Ice accretion is considered in four stages: rime, primary mixed, secondary mixed and glaze ice. Predictions match with existing models and experimental data in the limiting rime and glaze cases. The mixed ice formulation consequently however provides additional insight into the composition of the overall ice structure, which ultimately influences adhesion and ice thickness; and shows that for similar atmospheric parameter ranges, this simple mixed ice description leads to very different accretion rates. A simple one-dimensional energy balance was solved to show how this freezing fraction parameter increases with decrease in atmospheric temperature, with lower freezing fraction promoting glaze ice accretion.